Gender as “Ebola from Brussels”: The Anticolonial Frame and the Rise of Illiberal Populism. - Korolczuk, Elżbieta; Graff, Agnieszka (Signs: Journal of Women in Culture & Society)
An analysis of how antigenderism was effectively used by right-wing and religious fundamentalists to support the critique of gender equality movements as ideological colonization, is presented. Topics covered include how antigenderism contributes to the transnational resurgence of illiberal populism, depiction of religious conservatives as an embattled minority by illiberal populists, and role of the alliance between religious fundamentalists and illiberal populists in antigenderism.